The prognostic significance of microsatellite instability in colorectal cancer: a Swedish multi-center study - Rantanen, Petri; Keränen, Anne; Barot, Shabane; Ghazi, Sam; Liljegren, Annelie; Nordenvall, Caroline; Lindblom, Annika; Lindforss, Ulrik (International journal of colorectal disease, 2023)
Purpose About 10 to 15% of patients with sporadic colorectal cancer display mutations in DNA mismatch repair (MMR) genes shown as microsatellite instability (MSI). Previous reports of colorectal cancer (CRC) indicate a better prognosis for patients with MSI tumors compared to patients with microsatellite stable (MSS) tumors. In this study, our aim was to investigate whether MSI is an independent prognostic factor in CRC. Patients and methods Patients with stage I–III colorectal cancer and subject to curative surgery during 2002–2006 in the Swedish low-risk colorectal cancer study group cohort were eligible for inclusion. Deficient MMR (dMMR) status was analyzed by immunohistochemistry (IHC) and/or by MSI testing with polymerase chain reaction (PCR). Prognostic follow-up and treatment data were retrieved from patient records. Statistical analyses to assess MSI-status and prognosis were done using logistic regression and survival analyses using the Kaplan-Meier method and Cox regression hazards models adjusted for age, sex, stage, comorbidity, and tumor location. Results In total, 463 patients were included, MSI high tumors were present in 66 patients (14%), and the remaining 397 were MSS/MSI low. Within 6 years, distant recurrences were present in 9.1% and 20.2% ( P = 0.049), and death occurred in 25.8% and 31.5% in MSI and MSS patients, respectively. There was no statistically significant difference in overall mortality (HR 0.80, 95% CI 0.46–1.38), relapse-free survival (HR 0.82, 95% CI 0.50–1.36), or cancer-specific mortality (HR 1.60, 95% CI 0.73–3.51). Conclusion Despite distant metastases being less common in patients with MSI, there was no association between MSI and overall, relapse-free, or cancer-specific survival.